Selection and overview of benchmark sites in participating countries - Devendra, C. (International Livestock Research Institute, 1999)
The aim of this presentation is to provide a background to the process and outcomes that were involved in the selection of key benchmark sites (BMS) in participating countries (China, Indonesia, Philippines, Thailand and Vietnam). The criteria for the selection of BMS is listed and choice of BMS in rainfed areas in individual countries summarised in a table. Focus points include location, distance (Km), rainfall (mm), climate, agroecological zones (AEZ), animals, type of Crop Animal system and dry season (months).